Stacey's Extraordinary Words - Abrams, Stacey; Thomas, Kitt (New York, NY : Balzer + Bray, an imprint of HarperCollins Publishers, 2021)
When Stacey is chosen to compete in the local spelling bee, she learns that, win or lose, her words are powerful, and sometimes perseverance is the most important word of all.
Keywords: Abrams, Stacey -- Juvenile fiction; Abrams, Stacey -- Fiction; Spelling bees -- Juvenile fiction; Perseverance (Ethics) -- Juvenile fiction; Spelling bees -- Fiction; Perseverance -- Fiction; JUVENILE FICTION / Biographical / United States; JUVENILE FICTION / People & Places / United States / African American & Black; JUVENILE FICTION / Girls & Women; Perseverance (Ethics); Spelling bees; Biographical fiction; Picture books; Fiction; Juvenile works; Picture books